Comparison of stent patency between EUS-guided hepaticogastrostomy with bridging and endoscopic transpapillary biliary drainage for hilar obstruction - Takeshita, Kotaro; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Ohba, Akihiro; Kawasaki, Yuki; Takasaki, Tetsuro; Yagi, Shin; Agarie, Daiki; Hara, Hidenobu; Hagiwara, Yuya; Yamashige, Daiki; Okamoto, Kohei; Fukuda, Soma; Kuwada, Masaru; Chatto, Mark; Kondo, Shunsuke; Morizane, Chigusa; Ueno, Hideki; Saito, Yutaka; Okusaka, Takuji (Endoscopy International Open, 2024)
Background and study aims Endoscopic ultrasound-guided hepaticogastrostomy with bridging between the left and right bile ducts is an alternative to endoscopic transpapillary drainage for malignant hilar biliary obstruction. We aimed to analyze the long-term stent patency of endoscopic ultrasound-guided hepaticogastrostomy with bridging.Patients and methods Patients who underwent endoscopic ultrasound-guided hepaticogastrostomy with bridging between April 2018 and July 2023 were retrospectively analyzed. We retrospectively compared the stent patency of these patients with that of the individuals who underwent endoscopic transpapillary drainage-multi-stenting using unmatched (entire) and propensity score-matched cohorts.Results Endoscopic ultrasound-guided hepaticogastrostomy with bridging had a technical success rate of 90% (18/20). Adverse events were minimal. The number of clinical success cases was 17 and 82 for endoscopic ultrasound-guided hepaticogastrostomy with bridging using metallic stent and endoscopic transpapillary drainage-multi-stenting, respectively. The recurrent biliary obstruction rate was 17.6% and 58.5% for endoscopic ultrasound-guided hepaticogastrostomy with bridging and endoscopic transpapillary drainage-multi-stenting, respectively; the median time to recurrent biliary obstruction (days) was significantly longer for endoscopic ultrasound-guided hepaticogastrostomy with bridging in the entire (not reached vs. 104, P=0.03) and propensity score-matched (183 vs. 79, P=0.05) cohorts. The non-recurrent biliary obstruction rate for endoscopic ultrasound-guided hepaticogastrostomy with bridging was 91.6% at 3 and 6 months and 57% at 12 months. Multivariate analyses revealed that endoscopic ultrasound-guided hepaticogastrostomy with bridging contributed to a lower recurrent biliary obstruction incidence (hazard ratio, 0.31, P=0.05) without significant difference.Conclusions Stent patency was significantly better for endoscopic ultrasound-guided hepaticogastrostomy with bridging. However, future prospective studies are needed.
Keywords: Pancreatobiliary (ERCP/PTCD); Strictures; Endoscopic ultrasonography; Biliary tract; Intervention EUS